Analisis Perlakuan Akuntansi Transaksi Asuransi Syariah Pada Prudential Syariah Cabang Medan Berdasarkan PSAK No. 108 - Caroline Damima Johan; Rahmat Daim Harahap; Dini Aminta; Elvina Damayanti; Farhan Rizqi Bangko; Rizqia Amanda (Fakultas Ekonomi dan Bisnis Universita Labuhanbatu Sumatera Utara Indonesia, 2023)
This study aims to find out how the application of Islamic Insurance transaction accounting at Prudential Sharia Insurance is a comprehensive system in which participants donate (partially) part or all of their contributions that are used to pay claims on certain risks from unfortunate to the soul, body, or objects experienced by eligible participants. Accounting for Sharia Insurance Transactions has been regulated in PSAK No 108. This research object is done at Prudential Syariah. The method of analysis used is qualitative method with descriptive approach. The results showed that Prudential Syariah has not applied PSAK No. 108 completely on the preparation of financial statements. Prudential Syariah only prepares financial reports consisting of Cash Register Syariah Report, LBK Syariah Mutation Recap Report, and Sharia Cash Book Sheet. This is due to the policies in the company’s management in preparing financial statements in each of its subsidiary companies. This is caused the system of recording financial statements in branch office in a computerized and recapitalized data directly by the center.